Estimation of whole body moment of inertia using self-imposed oscillations - Damavandi, M.; Allard, P.; Barbier, F.; Leboucher, J.; Rivard, C. H.; Farahpour, N. (Ninth International Symposium on the 3-D Analysis of Human Movement, June 28-30, 2006, Valenciennes, France, 2006)
Able-bodied segment moment of inertia (MOI) can be determined from anthropometric tables and different models. These methods cannot be used for special populations such as obese subjects, elderly individuals, etc. The objectives of this study are to estimate the personalized in vivo moment of inertia of the whole body using three-dimensional (3-D) inverse dynamic and angular momentum approaches and compare their results to five other methods (Hanavan`s model, photogrammetry, two anthropometric tables, and inverse pendulum) tested in seven individuals. With respect to the modified Zatsiorsky method, the inverse dynamic approach values were within 3.7% of those along the all principal axes while the other four methods were off by 3.4%. The angular momentum method values were within 2.0% of the modified Zatsiorsky method for all three axes of rotation. It appears that the proposed methods could be applied to estimate the personalized in vivo moment of inertia of people with different body morphology.